Geometry of Freezing Impacts Ice Composition: Implications for Icy Satellites. Issue 3 (26th March 2023) - Buffo, J. J.; Meyer, C. R.; Chivers, C. J.; Walker, C. C.; Huber, C.; Schmidt, B. E.
Abstract: Non‐ice impurities within the ice shells of ocean worlds (e.g., Europa, Enceladus, Titan, Ganymede) are believed to play a fundamental role in their geophysics and habitability and may become a surface expression of subsurface ocean properties. Heterogeneous entrainment and distribution of impurities within planetary ice shells have been proposed as mechanisms that can drive ice shell overturns, generate diverse geological features, and facilitate ocean‐surface material transport critical for maintaining a habitable subsurface ocean. However, current models of ice shell composition suggest that impurity rejection at the ice‐ocean interface of thick contemporary ice shells will be exceptionally efficient, resulting in relatively pure, homogeneous ice. As such, additional mechanisms capable of facilitating enhanced and heterogeneous impurity entrainment are needed to reconcile the observed physicochemical diversity of planetary ice shells. Here we investigate the potential for hydrologic features within planetary ice shells (sills and basal fractures), and the unique freezing geometries they promote, to provide such a mechanism. By simulating the two‐dimensional thermal and physicochemical evolution of these hydrological features as they solidify, we demonstrate that bottom‐up solidification at sill floors and horizontal solidification at fracture walls generate distinct ice compositions and provide mechanisms for both enhanced and heterogeneous impurity entrainment. We compare our results with magmatic and metallurgic analogs that exhibit similar micro‐ and macroscale chemical zonation patterns during solidification. Our results suggest variations in ice‐ocean/brine interface geometry could play a fundamental role in introducing compositional heterogeneities into planetary ice shells and cryoconcentrating impurities in (re)frozen hydrologic features. Plain Language Summary: The ice shells of ocean worlds are not pure water ice but contain significant amounts of salts and other ocean‐derived impurities. These impurities are believed to play an important role in the dynamics, evolution, and habitability of ice‐ocean worlds. Additionally, observations of salts on the surfaces of these moons can inform us of their underlying ocean properties. That said, salts are not easily entrained into ice under the thermal and geometric (vertically downward freezing) conditions present at the ice‐ocean interfaces of these ice shells, leading to relatively pure ice, and necessitating an explanation for how the compositional variations observed in ice shells are introduced. Here we explore a possible solution: the freezing of water bodies within ice shells that have surfaces that freeze vertically upward (floors) and horizontally (walls). We find that these freezing geometries facilitate enhanced and spatially variable salt entrainment. Our results suggest that solidifying water bodies within ice shells could play a key role in explaining the compositional diversity observed on ice‐ocean world surfaces and that constraining the dynamics that govern these ice‐brine systems will be critical in linking spacecraft measurements of planetary ice compositions to the properties of subsurface water reservoirs. Key Points: When a brine freezes, the direction of solidification affects the structure and composition of the resulting ice Ice formation at sill floors and fracture walls provides a mechanism for heterogeneous and amplified impurity entrainment in ice shells Cryoconcentration of impurities in freezing hydrological features can impact ice shell material properties, geophysics, and habitability